The relationship between relief and geological structure in the river basin of Solina - Hadžimustafić, Edin; Babajić, Elvir; Ristanović, Branko; Mešanović, Dževad (Journal for Geography, 2019)
In this paper, within the framework of morphostructural features, relationship between relief and geological structure in the river basin of Solina (north-eastern Bosnia and Herzegovina) is analyzed. Main goal of this study is to investigate causal relationship between complex geological characteristics of the terrain and genesis, morphological evolution and differentiation of three relief units in the river basin of Solina. Relief of river basin of Solina is predominantly non-conformal, tectonically predisposed; its structure is dominated by Cretaceous - Paleogene clastites. In this paper are applied modern geomorphological-geological methods, field work, analysis of topographic and geological maps, as well as satellite images of the studied area. Presentation of data has been realized in the Geographic Information System, and the geospatial data were geo-visualized on two thematic maps.